Molecular Docking Studies of Some Hydroxy Nitrodiphenyl Ether Analogues as Tyrosinase Inhibitors - Fatemeh Sholehvar; Azizeh Asadzadeh; Hooria Seyedhosseini (Journal of Advanced Biomedical Sciences, 2016)
Background & Objective: Tyrosinase is a key enzyme in pigment synthesis.Overproduction of melanin in parts of the skin results in hyperpigmentation diseases. Thus, its inhibitors are highly important in the medical, cosmetic and agricultural fields. The aim of this research is the bioinformatical study of tyrosinase inhibition by a number of hydroxy nitrodiphenyl ether derivatives.